Clinicopathological assessment of renal tumors in pediatric age group in a sample of Iraqi patients: Clinicopathology of Pediatric Renal Tumors in Iraq - Ahmad, Elaf; Ban J. Qasim; Alaa G. Hussein (Iraqi Journal of Cancer and Medical Genetics, 2023)
Background: According to the Iraqi Cancer Registry, renal carcinoma is the 13th most common carcinoma, with 798 registered cases in 2020 and 418 deaths. Methods: This is a cross sectional retrospective study that includes the analysis of 116 randomly selected sample of pediatric patients (74 nephrectomies and 42 biopsies) sent to the Teaching Laboratories of AL-Emamain AL-Kadhmain city (AS), Baghdad medical city, and private laboratories from January 2019 to January 2023. Results: Histopathological diagnosis revealed a ratio from malignant to benign of 7.4:1. Wilm’s tumor was the most common malignant tumor (65.5%), while multicystic renal dysplasia was the most common benign tumor (7.8%). Abdominal pain was the most common clinical feature (67.2%), followed by abdominal mass (20.7%). Regarding malignant cases, Pathological stage I was the most common (39.0%). As for the histopathological subtype, triphasic type was the most common (57.1%), followed by the biphasic type (10.5%). Conclusions, Malignant tumors make up the vast majority of renal tumors. Wilm tumor is the predominant malignant tumor. Fortunately, most cases of Wilm tumors exhibited an early stage and favorable histology. Neuroblastoma was the second most common malignant tumor. The abdominal lump is the most common presentation of pediatric renal tumor.